PsycEXTRA Dataset 2010
DOI: 10.1037/e548132012-135
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychosocial adjustment during the post-radiation treatment transition

Abstract: The aim of this study was to examine the role of cognitive appraisal in predicting psychosocial adjustment during the post-radiation treatment transition. A predictive correlational design was used in a convenience sample of 80 patients with breast, lung, and prostate cancer who were receiving radiation therapy. Two weeks prior to completion of treatment, subjects completed instruments to measure symptom distress, uncertainty, cognitive appraisal, social support and selfefficacy for coping. The Psychosocial Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…The patients' needs change over time [22] and vary by disease site and stage [23] as well as treatment modality [24,25]. As the evidence grows supporting the multidimensional impact of cancer on supportive care needs [25,26], there is a growing appreciation of the importance of understanding the patterns and magnitude of unmet needs for different patient populations. Understanding the demand for service is an important basis for program planning and human resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' needs change over time [22] and vary by disease site and stage [23] as well as treatment modality [24,25]. As the evidence grows supporting the multidimensional impact of cancer on supportive care needs [25,26], there is a growing appreciation of the importance of understanding the patterns and magnitude of unmet needs for different patient populations. Understanding the demand for service is an important basis for program planning and human resource allocation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the degree of physical symptoms affected the patients' intentions to undergo cancer rehabilitation therapy, probably because greater physical symptoms and more pain are associated with decreased quality of life 24) and greater difficulty with psychosocial adaptation. 25) Cheville et al 26) conducted a survey of outpatient cancer patients and reported that 71.8% of cases experienced at least one physical symptom related to their cancer. To improve the quality of life of breast cancer patients, it is necessary to predict which patient will require rehabilitation, and administer therapy to those patients in a timely fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Αυτή η σταδιακή διαδικασία μπορεί να οδηγήσει σε προσαρμογή, δηλαδή μια φάση κατά την οποία ένα άτομο καταφέρνει να διατηρήσει την επιθυμητή ψυχοκοινωνική ισορροπία (Galica, 2008). Το φαινόμενο της ψυχοκοινωνικής προσαρμογής έχει μελετηθεί σε διαφορετικές μορφές οργανικής ασθένειας, όπως απώλεια όρασης (Jangra et al, 2007), η σκλήρυνση κατά πλάκας (Mazzarella, 2006;McNulty, Livneh, & Wilson, 2004), σωματική αναπηρία (Kocaman et al, 2007) και τον καρκίνο (Gumus, Cam, & Malak, 2011;Mazanec et al, 2011;Rizalar et al, 2014;Westbrook, 2005 (Bishop, 2005;Derogatis & Fleming, 1996;Linveh & Antonak, 1997 Lenz et al, 1997). Κάθε σύμπτωμα είναι πολυπαραγοντικό, ποικίλει σε ένταση, συχνότητα ή διάρκεια, στη δυσφορία που προκαλεί και τον τρόπο που περιγράφεται υποκειμενικά (Lenz et al, 1997).…”
Section: θεωρητικό μοντέλο της μετατραυματικής ανάπτυξηςunclassified